PENERAPAN STORY TELLING PADA MUSIC VIDEO BAND THE MUNCHEIS - Das, I Putu Gede Hari Dhanan Jaya; Puriartha, I Kadek; Tirtayasa, Desak Putu Yogi Antari (UPT Pusat Penerbitan LP2MPP ISI Denpasar, 2025)
This final project explores the application of storytelling techniques in the production of three music videos (MVs) by the band The Muncheis, namely “It Is What It Is,” “Freedom,” and “Friends.” The primary goal is to communicate the messages of the songs through a narrative and emotional visual approach. The creative process was carried out in three main stages: pre-production, production, and post-production. Pre-production involved lyric analysis, visual concept development, scriptwriting, and assembling the production team. Filming techniques such as handheld shots and warm color composition were used to enhance the emotional connection between the audience and the characters. Post-production processes, including rough cut, fine cut, picture lock, and color grading, were conducted to refine the final output. The results demonstrate that storytelling can enrich the emotional dimension of MVs and help audiences better grasp the intended messages, turning MVs into compelling narrative media beyond music promotion.